2004
DOI: 10.1038/sj.npp.1300505
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serotonin 5-HT2A Receptor-Stimulated Phosphoinositide Signaling in Fibroblasts from Melancholic Depressed Patients

Abstract: Abnormalities in serotonin (5-HT) receptors and 5-HT receptor-mediated signal transduction systems have been widely reported in mood disorders. This study was intended to evaluate 5-HT 2A receptor-coupled activation of phosphatidylinositol (PI) hydrolysis in subtypes of depression. Samples for fibroblast culture were obtained from patients with major depression with or without melancholia, and normal controls. Dose response curves were determined for 5-HT-induced PI hydrolysis. PI response was determined for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…These data are in line with the literature suggesting that fibroblasts could be a useful peripheral model for studying molecular processes in patients with neuropsychiatric disorders (Akin et al, 2004;Johansson et al, 2011;Auburger et al, 2012;Garbett et al, 2014;Kalman et al, 2014). In fact, fibroblasts are maintained in cultures in a controlled, reproducible environment, and after several rounds of cell division they are minimally affected by confounding factors (e.g., lifestyle or medication use) to which, in contrast, PBCs are exposed (Akin et al, 2004;Auburger et al, 2012;Garbett et al, 2014;Kalman et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…These data are in line with the literature suggesting that fibroblasts could be a useful peripheral model for studying molecular processes in patients with neuropsychiatric disorders (Akin et al, 2004;Johansson et al, 2011;Auburger et al, 2012;Garbett et al, 2014;Kalman et al, 2014). In fact, fibroblasts are maintained in cultures in a controlled, reproducible environment, and after several rounds of cell division they are minimally affected by confounding factors (e.g., lifestyle or medication use) to which, in contrast, PBCs are exposed (Akin et al, 2004;Auburger et al, 2012;Garbett et al, 2014;Kalman et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Depression subtypes show excessively fixed symptoms at extremes of function (for example, overactive or inhibited appetite). Melancholic severity and elevated suicidality (Grunebaum et al, 2004) have been related to defective second messenger systems coupled to the-serotonin-2a receptor (Akin et al, 2004), a mechanism that profoundly alters physiologic variability. Melancholia disrupts anterior cingulate function (Rogers et al, 2004), a correlate of mental slowness and cognitive deficits that also represent a lack of functional variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analyses did not suggest such a possible influence on 5-HT 2A receptor BI in the cortical areas examined. Indeed, not all studies demonstrated an impact of these psychotropic drugs (Leysen et al 1987;Messa et al 2003), and if they did, instead of a down-regulation, an up-regulation of 5-HT 2A receptors could be expected (Zanardi et al 2001;Akin et al 2004). Since increased 5-HT 2(A) receptor BI has been reported post-mortem in the frontal cortices of suicide victims , it is also important to point-out that no suicide attempt had occurred in our sample at least 6 months prior to this study.…”
Section: Frontal Cortexmentioning
confidence: 99%